Conceptual instrumentation of washing machine for conformity to the Islamic laws of Syarak - Ibrahim, Basri; Haji Razali, Mohd. Hudzari; Othman, Mohd Shahril; Muhammad, Hasbullah (2013)
The concept of today’s washing machine that uses control technology to clean clothing is based on clothing weight factor proportionately to the amount of water used irrespective of the nature of the contaminants. However according to Islamic law, clothing such as being contaminated with children’s urine for an example has to be cleaned using continuous flowing water especially during the initial stage of washing. With the concept of algorithm system and integrated into the washing machine, the continuous running water will be subjected during the initial wash and spin option. The light sensors used on both inlet and outlet valve will ensure the contaminated solids or liquids will be accordingly removed. Application of solenoid valve is used to control the water tank level during washing and drying period. Similar concept has been developed at Farm Unit, Department of Agriculture Science, UniSZA for removing the toxin from food tuber of Dioscorea hispida before it can consume securely. The analysis shows that using flowing new water will remove toxicity which was represent of excrement in clothing. This paper elaborates the concept of automatic washing machine operation which complies with Islamic law of syarak.